Definition & Pathophysiology of Sepsis - Dr. Devendra Prasad K J; Dr. Ravishankar (Story of Sepsis, Edition 1, 2025)
The comprehension of sepsis has considerably advanced since its initial presentation in 1991, which primarily concentrated on the criteria for systemic inflammatory response syndrome (SIRS). SIRS is defined by systemic inflammation, evident through manifestations such as irregular temperature, tachycardia, and fluctuations in white blood cell counts. Modern interpretations depict sepsis as a multifaceted syndrome, previously termed hypercytokinemia, characterized by the excessive production of inflammatory cytokines. This evolution in understanding recognizes that sepsis can emerge from infections, surgical trauma, and a range of non-infectious elements, thus complicating both diagnostic and therapeutic approaches. The reconceptualization of sepsis as a systemic inflammatory response correlated with suspected or confirmed infections has deepened the comprehension of its pathophysiology, necessitating the introduction of more stringent diagnostic criteria. Ultimately, the evolution of sepsis definitions signifies a shift from a fundamental SIRS-focused perspective to a more inclusive framework that encompasses a diverse array of triggers and responses, underscoring the persistent need for research and modifications in clinical practice.